2022
DOI: 10.1109/access.2022.3156639
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cooperative Game and Cooperative Operation of Multi-Level Supply Chain Under Background of Carbon Emission Reduction

Abstract: In the context of global efforts to develop low-carbon economy and curb the growth of fossil energy, it is particularly important for supply chain enterprises to make scientific decisions on emission reduction and energy conservation. This paper investigates supply chain enterprises to make emission reduction decisions by considering cost-benefit of carbon emission reduction and internal and external factors changes. We analyze the dynamic game model of a three-level supply chain consisting of suppliers, manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Despite the fact that these practices were found to improve firms' environmental performance, the role of digital technologies, like I 4.0 technologies, can never be overemphasized regarding the effective implementation of the practices. For example, one of the GSCMP is Environmental Data disclosure and transparency [63,93]. Implementation of this GSCMP indeed could prove difficult without proper digital technologies like the I 4.0 s blockchain enabling it.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that these practices were found to improve firms' environmental performance, the role of digital technologies, like I 4.0 technologies, can never be overemphasized regarding the effective implementation of the practices. For example, one of the GSCMP is Environmental Data disclosure and transparency [63,93]. Implementation of this GSCMP indeed could prove difficult without proper digital technologies like the I 4.0 s blockchain enabling it.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have discussed the ways of enterprise cooperation and its impact on carbon emission reduction [ 78 , 79 , 80 ] but the improvement of enterprise cooperation awareness is inseparable from the government’s guidance [ 81 ]. Apart from this, when the region implements the coordinated joint carbon reduction model, the carbon emission reduction efforts of enterprises can also reach the peak [ 82 ], showing that the interaction of carbon emission reduction between regions can send signals to enterprises, and then promote the interaction and cooperation between regional economy, industry, and enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that compared with the non-cooperative situation, supply chain members will make more emission reduction efforts and gain more economic profits in a cooperative situation. By constructing a three-echelon supply chain and applying a differential game model, Chen et al (2022) found that product emission reduction in the cooperative mode is higher than that in the non-cooperative mode. Cooperative emission reduction is better for the supply chain to achieve its carbon reduction targets.…”
Section: Carbon Emission Reductions Through Supply Chain Cooperationmentioning
confidence: 99%